Adsorptive removal of toxic crystal violet dye from aqueous solutions using buckwheat/Fe3O4 composites - Gazdagli, Irem; Isik, Birol; Cakar, Fatih; Cankurtaran, Ozlem (SPRINGER HEIDELBERG, 2025)
The contamination of industrial wastewater with dyes is a significant public health issue in numerous countries and necessitates the use of sophisticated treatment methods. The creation of magnetite-doped adsorbents derived from biomass is highly desirable for their ability to efficiently eliminate contaminants from solutions. This development holds significant importance in terms of enhancing the environment, reducing expenses and process complexity, and ensuring human well-being. This work aimed to prepare buckwheat-magnetite composites as a possible adsorbent for efficiently eliminating the hazardous crystal violet (CV) dye from aqueous solutions. The adsorbents were characterized by the use of FTIR-ATR, SEM, EDX, zeta potential, VSM, and XRD analyzes. Several adsorption parameters were examined, such as contact time (0-150 min), starting concentration in the dye (10-50 mg/L), adsorbent dosage (0.2-6.0 g/L), pH (2-12), and temperature dependence (298-318 K). The optimum values of the operational factors for buckwheat/Fe3O4(1%) composite adsorbent were determined as contact time: 60 min, adsorbent dosage: 1.0 g/L, agitation rate: 120 rpm, initial pH: approximately 7. The influence of monovalent and divalent salt concentration onto adsorption process was performed. The Langmuir model is a crucial factor in determining balance adsorption experiments. In this case, a composite including buckwheat adsorbent with a concentration of 625.00 mg/g and buckwheat/Fe3O4(1%) composite adsorbent at a temperature of 298 K has a maximum absorption capacity of 680.27 mg/g for CV dye. The CV dye kinetics are appropriate for the pseudo-second-order kinetic model. Furthermore, as per the intraparticle diffusion concept, the adsorption process occurs in three distinct stages. Moreover, the thermodynamic characteristics obtained from the measurements indicate that the adsorption of organic dye onto the buckwheat adsorbent is both endothermic (Delta H-o = 4.89kJ/mol) and spontaneous (Delta G(o )= -28.69kJ/molat298K). However, it has been discovered that buckwheat-magnetite composite exhibits exothermic (Delta H-o = -23.55kJ/mol) and spontaneous (Delta G(o )= -27.34kJ/molat298K) behavior when used as composite adsorbents. Consequently, buckwheat and buckwheat-magnetite composite adsorbents can function as very efficient adsorbers for dye removal in industrial effluent.
Keywords: Adsorption; Buckwheat; Composite; Crystal violet; Magnetite; CATIONIC DYES; MALACHITE GREEN; METHYLENE-BLUE; ORGANIC-DYES; LEAD II; WASTE; POWDER; WATER; NANOPARTICLES; EQUILIBRIUM; Energy & Fuels; Engineering